Piezoelectricity In Technical Practice - Škarabelová, Lenka (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
Bachelor's thesis is dedicated to the study of the principle and possibilities of use of the piezoelectric effect. Since the use of piezoelectric effect in electrical engineering is very extensive, the main focus is placed on the ability to exploit this effect in the field of ultrasonic and piezoelectric resonators. Next aim of this work is practically and theoretically to get acquainted with the measurement with an ultrasonic equipment from company Olympus and ultrasonic defectoscopy for detection of possible imperfections in the material and their evaluation.
Keywords: Piezoelectric effect; Ultrasonic defectoscopy; Piezoelectric effect in technical engineering; Ultrasonic